Temporal variability on Seagrass Cover and Species Composition in a Tourism Hotspot: A case study in Derawan Island - Kusumaningtyas Mariska Astrid; Zulfikar Andi; Rustam Agustin; Salim Hadiwijaya L.; Rahayu Yusmiana P.; Daulat August; Suryono Devi Dwiyanti; Ati Restu Nur Afi; Sudirman Nasir; Khairunnisa Khairunnisa; Hidayat Wahyu (BIO Web of Conferences)
Seagrass ecosystems in Derawan Island provide crucial services to coastal communities, including serving as a food source for sea turtles. However, like many coastal areas, seagrass ecosystem in Derawan Island faces significant challenges. One major issue is related to tourism, which affects seagrass both through land use changes for tourism development and through various tourism activities. This study aims to assess the resilience of the seagrass ecosystem on Derawan Island by examining temporal variability in seagrass cover and community structure. Permanent plots were established to monitor changes in seagrass cover and community composition. The observations were conducted following the SeagrassWatch method. Data were collected three times, in September 2018, March 2019, and August 2019. Seagrass cover during 3 times monitoring showed fluctuate trend (averaging 42.3%, 33.2%, and 32.3%, respectively). Pioneer species such as H. pinifolia dominated the seagrass meadow, maintaining a consistently higher cover compared to other species. Conversely, the species T. hemprichii was observed at lower levels, likely due to overgrazing by sea turtles, which may have prevented its recovery. This study provides valuable insights into the status and resilience of seagrass ecosystems in a tourism hotspot and offers information that could be useful for managing seagrass ecosystem on Derawan Island.